2019
DOI: 10.1126/science.aav7541
|View full text |Cite
|
Sign up to set email alerts
|

Packing of apolar side chains enables accurate design of highly stable membrane proteins

Abstract: The features that stabilize the structures of membrane proteins remain poorly understood. Polar interactions contribute modestly, and the hydrophobic effect contributes little to the energetics of apolar side-chain packing in membranes. Disruption of steric packing can destabilize the native folds of membrane proteins, but is packing alone sufficient to drive folding in lipids? If so, then membrane proteins stabilized by this feature should be readily designed and structurally characterized—yet this has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 77 publications
6
89
0
Order By: Relevance
“…This indicates a strict steric requirement for van der Waals packing interactions between TM domain side chains that dictates the stability and regulation of the αvβ3 resting state. Similar Ile-Leu mutations have been observed to abrogate select TM domain interactions for shorter engineered TM peptides (34,35), yet it is noteworthy to find a similar result within a large protein complex interacting simultaneously through several extramembrane domains. The mutational consequences might also be rationalized in the context of previous reports for small-x 3 -small motifs.…”
Section: Discussionmentioning
confidence: 54%
“…This indicates a strict steric requirement for van der Waals packing interactions between TM domain side chains that dictates the stability and regulation of the αvβ3 resting state. Similar Ile-Leu mutations have been observed to abrogate select TM domain interactions for shorter engineered TM peptides (34,35), yet it is noteworthy to find a similar result within a large protein complex interacting simultaneously through several extramembrane domains. The mutational consequences might also be rationalized in the context of previous reports for small-x 3 -small motifs.…”
Section: Discussionmentioning
confidence: 54%
“…Notably, previous experiments which truncated the polar upper-TM region of an engineered, watersoluble form of PLB found that this also served as a switch from pentamer to tetramer, which could suggest a greater role for polar forces in higher-order PLB oligomerization (Slovic, Lear et al 2005). However, emerging research has also continued to demonstrate the prominent role of van der Waal forces in stabilizing peptide oligomers and an engineered PLB-like molecule devoid of strongly polar residues has even been shown to easily stabilize as a pentamer (Mravic, Thomaston et al 2019), which we suggest is secondary to hydrophobic zipper interactions. The evidence presented here show PLB and SLN as examples supporting the prominent role of hydrophobic interactions in small peptide oligomerization as well as determination of oligomer order.…”
Section: Novel Structural Insights Into Sln and Plb Self-assemblymentioning
confidence: 99%
“…Automating modelling and design processes and extending them to complex membrane proteins will likely require an accurate energy function that correctly balances intra-protein interactions, membrane solvation and water solvation 13,14 .…”
Section: Introductionmentioning
confidence: 99%